Microscopic calculations of effective charges and quadrupole transition rates in Si, S and Ar isotopes. - Radhi, R. A.; Ali, A. H. (Iraqi Journal of Science, 2022)
Quadrupole transition rates and effective charges are calculated for even-even Si,S and Ar isotopes based on sd and sdpf -shell model spaces. Shell modelcalculations are performed with sd shell-model space for neutron number (N) ≤ 20and sdpf shell-model space for N > 20. Excitation out of major shell space are takeninto account through a microscopic theory which allows particle-hole excitationfrom the core and model space orbits to all higher orbits with 2 excitation.Effective charges are obtained for each isotope. The results show a systematicincrease in the B(E2) values for N 20. Shell model calculation predicts the erosionof the N=28 magicity in the neutron rich 42Si. No clear indications about the erosionof the shell gap closure in 44S and 46Ar isotope.